ANALISIS INSOMNIA PADA PENDERITA DIABETES MELITUS - Wahyuningsih, Atik Setiawan (STRADA : Jurnal Ilmiah Kesehatan, 2017)
Rest of sleep regulates insulin and glucose tolerance during night-time. Patients with DM often suffer insomnia due to metabolic disorders such as osmotic diuresis and dehydration as manifested by nocturia, stress, anxiety, increased cortisol and decreased GH. Cortisol converts protein into glucose. This research objective is to identify incident of insomnia to patients with diabetes mellitus (DM) and identify the characteristics of insomnia to patients with DM in CHC Balowerti Kediri. Research design was descriptive. Samples were total sampling. Measuring instrument used Insomnia Severity Index (ISI), and then analyzed using distribution frequency. 65 patients with DM suffered insomnia from 79 responden with DM. Highest level of patients with DM suffered insomnia. Health workers are expected to provide additional information about insomnia to patients with DM and treatment for that.